2020
DOI: 10.3390/nano10010120
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Surface Colonization of Antibacterial and Bioactive Materials Doped with Strontium and/or Silver Ions

Abstract: Nowadays, there is a large amount of research aimed at improving the multifunctional behavior of the biomaterials for bone contact, including the concomitant ability to induce apatite formation (bioactivity), fast and effective osteoblasts colonization, and antibacterial activity. The aim of this study is to develop antibacterial and bioactive surfaces (Ti6Al4V alloy and a silica-based bioactive glass) by chemical doping with strontium and/or silver ions. The surfaces were characterized by Scanning Electron Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…No significant differences can be evidenced among the tested glasses in terms of hydroxylation upon contact with SBF up to 3 days. Moreover, a signal around 1200 cm –1 , attributable to silica gel formation, and one at 1035 cm –1 , associated with P–O stretching, can be observed on all the glasses from 1 day of soaking ( Figure 3 b), 28 , 29 evidencing the bioactivity of all the tested compositions. A doublet around 600–560 cm –1 , correlated to P–O stretching, 26 , 27 started to appear on SCN 50-35-15 after 3 days of soaking ( Figure 3 c), confirming its faster hydroxyapatite precipitation.…”
Section: Resultsmentioning
confidence: 84%
“…No significant differences can be evidenced among the tested glasses in terms of hydroxylation upon contact with SBF up to 3 days. Moreover, a signal around 1200 cm –1 , attributable to silica gel formation, and one at 1035 cm –1 , associated with P–O stretching, can be observed on all the glasses from 1 day of soaking ( Figure 3 b), 28 , 29 evidencing the bioactivity of all the tested compositions. A doublet around 600–560 cm –1 , correlated to P–O stretching, 26 , 27 started to appear on SCN 50-35-15 after 3 days of soaking ( Figure 3 c), confirming its faster hydroxyapatite precipitation.…”
Section: Resultsmentioning
confidence: 84%
“…A recent study reported that Sr 2+ is released from surfaces when in contact with fluids. Once released it is an activator of the osteoblasts because it activates calcium receptors: it can positively contribute to reduce the risk of bacterial colonization by promoting an early adhesion of the osteoblasts and can also counteract the cytotoxic effect of other ions such as Ag (Cochis et al, 2020) or Mg (Gao et al, 2019), whether the Sr is a co-dopant element. For this excellent property of promoting bone growth, thus inhibiting osteoclasts activity, it can be involved in the treatment of osteoporosis (Frasnelli et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…After cytocompatibility and antibacterial assays, the following optimal (intended as safe for cells and effective toward bacteria) AMPs concentrations were selected and used in further experiments: Nisin 75 µg/ml and LL-37 10 µg/ml. To verify the antibacterial activity of the targeted AMPs a cells-bacteria coculture assay was performed as in our previous studies (Jekabsone et al, 2019;Cochis et al, 2020). The co-culture method was designed to monitor the viability of both cells and bacteria that are challenging in the same environment for the same surface colonization, thus allowing for the validation of the AMPs' targeted activity toward bacteria (Cochis et al, 2020).…”
Section: Co-culturesmentioning
confidence: 99%
“…After the evaluation of AMPs cytocompatibility and antibacterial activity, the following concentrations were selected as the most promising in reducing the pathogen metabolism while preserving the cell viability that was considered as the key factor in this study: 75 µg/ml Nisin and 10 µg/ml LL-37. However, those results were obtained by keeping separated cells and bacteria in different environments; so, to check whether the AMPs activity was really targeting only (or at least mainly) bacteria, a co-culture assay was performed as we have previously described (Jekabsone et al, 2019;Cochis et al, 2020) to evaluate the AMPs performance in the same environment containing both cells and bacteria. Therefore, it should be clarified that only the number of adherent bacteria was evaluated as suggestive for those able to colonize the same surface as cells when cultivated in the same environment.…”
Section: Co-culturesmentioning
confidence: 99%